Research on Strategies to Enhance Semiconductor Thin-film Solar Cells Efficiency - Gao, Ya; Yu, Sha'er; Liu, Ziyan (Transactions on Environment, Energy and Earth Sciences, 2024)
Recently, advanced solar cells are becoming growing essentially in the world due to their environmentally friendly and renewable, and new semiconductor thin film solar cells are gradually entering lives of people. Therefore, this paper mainly focuses on methods to enhance the performance of semiconductor thin-film solar cells. Elemental doping and modification techniques can change the properties of a semiconductor by doping the intrinsic semiconductor with specific elements and realizes the conductivity modulation of semiconductor thin film cells. Internal structure optimization can optimize the internal structure of the cell, through the optimization of the cell buffer layer or absorption layer to ameliorate battery performance. It is possible to insert insulating layers between internal structures or to optimize film absorbing and buffer layers. Solar cell transfer efficiency can be improved by these methods. Most importantly, these methods can significantly alleviate the environmental and energy pressures.